2022
DOI: 10.1186/s12885-022-09861-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral mcDNA-mediated bispecific CAR T cells kill tumor cells in an experimental mouse model of hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the adoptive immunotherapy of which is worth studying. CD133, a kind of cancer stem cell (CSC) antigen, together with glypican-3 (GPC3) has been proved to be highly expressed in HCC cells and both of them are used as targets to generate chimeric antigen receptor (CAR) T cells. But there are limitations like “off-target” toxicity, low transfection efficacy and weak antitumor ability in CAR T cells treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 51 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…These methods are broadly categorized into five categories, namely supervised methods, incorporating L1 regularized Cox regression 29 , RSF algorithm 29 , Cox regression 103 , least absolute shrinkage and selection operator (lasso) regression 120 , cascaded Wx 105 , recursive feature elimination 38 , Boruta 31 , Akaike information criterion (AIC) regression 114 , variance 72 , lasso analysis 40 , multivariate regression 40 , Chi-squared 118 , mutual information 118 , and ANOVA 39,118 . Additionally, Network based methods include network based stratification (NBS) 83 , weighted correlation network analysis (WGCNA) 86 , canonical correlation analyses (CCA) 67 , patient similarity networks 38 , and neighborhood component analysis (NCA) 23 . Dimensionality reduction methods include non-negative matrix factorization (NMF) 40 , autoencoders (AEs) 28 , variational autoencoders (VAEs) 43 , principal component analysis (PCA) 39 , and dominant effect of the cancer driver genes (DEOD) 75,132 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are broadly categorized into five categories, namely supervised methods, incorporating L1 regularized Cox regression 29 , RSF algorithm 29 , Cox regression 103 , least absolute shrinkage and selection operator (lasso) regression 120 , cascaded Wx 105 , recursive feature elimination 38 , Boruta 31 , Akaike information criterion (AIC) regression 114 , variance 72 , lasso analysis 40 , multivariate regression 40 , Chi-squared 118 , mutual information 118 , and ANOVA 39,118 . Additionally, Network based methods include network based stratification (NBS) 83 , weighted correlation network analysis (WGCNA) 86 , canonical correlation analyses (CCA) 67 , patient similarity networks 38 , and neighborhood component analysis (NCA) 23 . Dimensionality reduction methods include non-negative matrix factorization (NMF) 40 , autoencoders (AEs) 28 , variational autoencoders (VAEs) 43 , principal component analysis (PCA) 39 , and dominant effect of the cancer driver genes (DEOD) 75,132 .…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive analysis of feature engineering methods across a range of disease-specific survival prediction studies unveils that supervised methods, such as Cox regression, L1 regularized Cox regression, and RSF algorithm, have been prevalent in diseases like ASCVD, trauma, and ovarian cancer 103,120 . On the other hand, network based methods including NBS and WGCNA, have been applied in diseases like KIRP, and hepatocellular carcinoma, which shows the significance of network structures in certain medical contexts 86 . Univariate analyses, including ANOVA, chi-squared, and univariate Cox regression, have been prevalent in diseases such as pancreatic cancer and heart failure, underscoring the significance of statistical testing in identifying relevant features 71,118 .…”
Section: Resultsmentioning
confidence: 99%
“…To overcome single antigen CAR-T cell antigen escape, lack of affinity and off-target toxicity, two markers specifically expressed in hepatocellular carcinoma might be good choices (GPC3 and CD133). It was found that bispecific CAR-T cells (CoG133-CAR T) were successfully transformed with a nonviral minicircle DNA (mcDNA) vector and achieved good lysis results [77]. Targeting two or even multiple antigens may be a new direction for future CAR-T cell research.…”
Section: Car-t Drug Name Companymentioning
confidence: 99%
“…117,118 This can be performed by administering a combination of two different CAR-transduced T-cell populations in a specific ratio (NCT03620058). 29,30 Another possible approach is the transduction of T-cells with two viral vectors encoding for two different CAR [30][31][32] or the transduction of TCR-specific T-cells with a CAR to generate dual-targeting T-cells. 33 In such situations, each CAR/TCR is intact and can mediate full activation upon antigen contact.…”
Section: Prevention Of Treatment-associated Toxicitymentioning
confidence: 99%